DESIGN OF PLUMBING SYSTEMS AND WASTE SHAFTS FOR APARTMENT ON SUDIRMAN STREET, BANDUNG CITY - Vitra Dennisa Antoni, Aura
The apartment building on Sudirman Street, Bandung, is designed in response to the main issue of future living, which is closely related to population growth. This project is located related to population growth. This project is located on Sudirman Street, covering an area of 9.477 m2 and consists of a total of 16 floors. The piping design for this building complies with the technical standards outlined in SNI 8135:2015 on Plumbing Systems. The design includes clean water systems, wastewater systems, vent systems, rainwater systems, hot water systems, fire protection systems, and waste management systems. In this apartment building, the shaft used for the residential area is located between two rooms. The clean water requirement for the apartment building on Sudirman Street, Bandung, is 853 m3 with 460 m3 needed for plumbing fixtures and 363 m3 for the fire protection system. The groundwater tank for clean water and fire protection is combined to optimize land use. In addition to clean water, there is also a recycled water system with a requirement of 132 m3 , which is used for flushing toilets throughout the building. The pipe dimensions for clean water range from 20 to 150 mm, with 20 to 25 mm for horizontal pipes and 38 to 150 mm for vertical pipes. For greywater, which is the source of recycled water, the discharge is 282,20 m3 /day with pipe diameters ranging from 32 to 150 mm, with 32 to 100 mm for horizontal pipes and 150 mm for vertical pipes. For blackwater, the discharge is 202,24 m3 /day with pipe dimensions ranging from 38 to 150 mm, divided into 38 to 75 mm for horizontal pipes and 75-150 mm for vertical pipes. Both greywater and blackwater pipes are serviced by loop-type vent pipes with sizes ranging from 32 to 200 mm. The fire protection system in the apartment building includes an automatic sprinkler system and hydrants, with a water requirement of 363 m3 , 38 hydrants, and sprinkles distributed across all floors of the building. Waste disposal is handled using a trash chute with dimensions of 60 x 60 cm, made of fire-resistant material. The total waste generated is .1.635 liters. The cost of constructing the plumbing and waste disposal system is Rp 24.997.659.000 with annual operational costs of Rp 5.731.172.000. Based on the economic feasibility analysis of NPV and BCR, this project is economically viable.